ANALISIS NILAI MORAL YANG TERKANDUNG DALAM CERITA RAKYAT ASAL USUL TERJADINYA BLEDUG KUWU - Nina Zulyana; Amalleina Fatiha; Oktaviana Indah Susanti; Maulana Ichsan; Mohammad Kanzunnudin (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
This study aims to analyze the moral values in the legendary folklore of Bledug Kuwu. The research method used is a qualitative descriptive approach with data collection through observation, interviews, and note-taking. Primary data was obtained through interviews, while secondary data was obtained from related folklore journals and books. The analysis was carried out using narrative analysis method. The results of the study show that the Ngelap Berkah tradition associated with the Bledug Kuwu legend contains valuable moral values such as cleanliness, cooperation, respect, connectedness to nature, and local wisdom. This tradition provides benefits for people's daily lives in creating harmony, responsibility, and concern for the environment and culture. This research provides an understanding and appreciation of moral values in the tradition of Bledug Kuwu's Bledug Berkah legend, which is an important foundation in shaping the identity and quality of people's lives.